Bank lending channel of monetary transmission effect towards Malaysian commercial banks after global financial crisis / Muhammad Syahmi Mohd Radzi - Mohd Radzi, Muhammad Syahmi (2015)
This paper investigates Bank Lending Channel of Monetary transmission effect towards Malaysian Commercial banks after global financial crisis. The factors that will be used in this research like the Bank Asset, Bank Liquidity and Bank Capital. The bank loan supply will act as the dependent variable. The data that I collected was from the year 2009 until 2014.